PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK BREADLIFE DI MALL LEMBUSWANA SAMARINDA - Abednego Suruanto Putranda Pali (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Bread is a necessity that is sought after by young to old people. The level of demand for bread in various region is very large and is one of them. In samarinda bread sales market there is a tight competition so that many businesses to increase sales to survive. This makes product quality and and promotion important enough to continue to innovate in offering a product. In this study there are two independent variables (free) including product quality and promotion. While the dependent variable is the purchase decision. The pusrpose of this study was to find out and analyze the influence of product quality variables and promotion influential simultaneously and partially on Breadlife product purchasing decisiuns at Mall Lembuswana Samarinda. To find out which variables have dominant influence on Breadlife product purchasing decisions at Mall Lembuswana Samarinda. The method used is a method with a sample of 96 respondents with an unknown population. Data collection techniques are libreary research and field research in thefrom of questionnaires, observations and interviews. Whhile the data analysis technique uses multiple linear analysis. The results of this study note that Product Quality (X1) and Promotion (X2) at Breadlife Mall Lembuswana Samarinda Simultaneously and partially have a significant influence on the decision to purchase Breadlife products at Mall Lembuswana Samarinda at 51.1%.